From Coercion to Compensation: Institutional Responses to Labour Scarcity in the Central African Copperbelt - Dacil Juif; Ewout Frankema (African Economic History Network (AEHN), 2016)
There is a tight historical connection between endemic labour scarcity and the rise of coercive labour market institutions in former African colonies. This paper explores how mining companies in the Belgian Congo and Northern Rhodesia secured scarce supplies of African labour, by combining coercive labour recruitment practices with considerable investments in living standard improvements. By reconstructing internationally comparable real wages we show that copper mine workers lived at barebones subsistence in the 1910s-1920s, but experienced rapid welfare gains from the mid-1920s onwards, to become among the best paid manual labourers in Sub-Saharan Africa from the 1940s onwards. We investigate how labour stabilization programs raised welfare conditions of mining worker families (e.g. medical care, education, housing quality) in the Congo, and why these welfare programs were more hesitantly adopted in Northern Rhodesia. By showing how solutions to labour scarcity varied across space and time we stress the need for dynamic conceptualizations of colonial institutions, as a counterweight to their oft supposed persistence in the historical economics literature.
Keywords: N17; N27; N37; N47; 330; Labour; Coercion; Central Africa; Copperbelt; Institutions